A Cluster Randomized Controlled Trial of a Dental Health - Helen V. Worthington, MSc, PhD, FIS; Kirsty B. Hill, BAY MSc; Jeanette Mooney, BA; (Blackwell Synergy, 2000)
Using a cluster randomized trial, this study tested the effectiveness of a dental health education program designed to improve the oral hygiene and dental knowledge of 10-year-old children.